2014
DOI: 10.1002/cbin.10257
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of Notch signaling in osteogenic differentiation of periodontal ligament stem cells in osteoporotic rats

Abstract: Estrogen deficiency-induced osteoporosis typically occurs in postmenopausal women and has been strongly associated with periodontal diseases. Periodontal ligament stem cells (PDLSCs) isolated from the periodontal ligament can differentiate into many types of specialized cells, including osteoblast-like cells that contribute to periodontal tissue repair. The Notch signaling pathway is highly conserved and associated with self-renewal potential and cell-fate determination. Recently, several studies have focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Correspondingly, DAPT treatment of human MSCs did not alter their alkaline phosphatase activity and mineralization relative to control cells (38). In contrast, DAPT-treated rat periodontal ligament stem cells exhibited a decrease of mineral deposition when cultured in osteogenic medium (39). Thus, the regulation of osteogenic differentiation by Notch signaling may be cell type-specific.…”
Section: Discussionmentioning
confidence: 87%
“…Correspondingly, DAPT treatment of human MSCs did not alter their alkaline phosphatase activity and mineralization relative to control cells (38). In contrast, DAPT-treated rat periodontal ligament stem cells exhibited a decrease of mineral deposition when cultured in osteogenic medium (39). Thus, the regulation of osteogenic differentiation by Notch signaling may be cell type-specific.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, our group showed that immobilized Jagged1 promoted osteogenic and neurogenic differentiation in hPDLSCs, depending on the culture conditions . Jagged1 upregulation was observed during osteogenic differentiation of rat PDLs . These results imply the role of Jagged1 in the osteogenic differentiation of PDL cells.…”
mentioning
confidence: 76%
“…Several molecular signaling pathways are of interest in PDLSC biology, including Notch, Wnt and BMP signaling. The Notch signaling pathway is known to play a crucial role in the osteogenic differentiation of PDLSC, as determined in rat studies [35] . Notch signaling is associated with self-renewal and cell-fate determination, with both mRNA and protein expression of Notch1 and Jagged1 upregulated when PDLSC were cultured in osteogenic conditions [35] .…”
Section: Profiling and Identitymentioning
confidence: 96%
“…The Notch signaling pathway is known to play a crucial role in the osteogenic differentiation of PDLSC, as determined in rat studies [35] . Notch signaling is associated with self-renewal and cell-fate determination, with both mRNA and protein expression of Notch1 and Jagged1 upregulated when PDLSC were cultured in osteogenic conditions [35] . Inhibition of Notch signaling in PDLSC, via treatment with γ-secretase inhibitor (a protease that cleaves the Notch protein), showed decreased osteogenic differentiation [35] .…”
Section: Profiling and Identitymentioning
confidence: 96%
See 1 more Smart Citation